Comparação entre imagens digitais diretas e laser de diodo na detecção de cáries proximais e oclusais - Araujo, Elaine Aparecida Félix de [UNESP] (2004)
The purpose of this study was to evaluate the accuracy of approximal and occlusal caries detection comparing Visualix and RVG CCD-based digital image with laser DIAGNOdent Sixty-six extracted posterior teeth were imaged under identical standardized geometric and exposure conditions. Four examiners, using five point confidence scale, rated 132 proximal and 66 occlusal surfaces for the presence or absence of carious lesions by means of three diagnostic systems: a) Visualix; b) RVG; c) DIAGNOdent. The gold standard was determined by microscopy analysis of sections. Receiver Operating Characteristic curves were generated analyzed with Kappa the according intra and interexaminers. The results indicated that digital images were better to detection approximal caries than laser Diagnodent and similar to occlusal caries